2014
DOI: 10.1007/s00540-014-1891-x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of pulmonary embolism and deep vein thrombosis and their predictive risk factors after lower extremity arthroplasty: a retrospective analysis based on diagnosis using multidetector CT

Abstract: This observational study showed that the overall incidence of VTE after THA and TPKA is 4.4 % in patients receiving recommended antithrombotic prophylaxis. TPKA is associated with a higher incidence of VTE than of THA, and greater BMI and older patient age are also independent risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…First, the mean age of participants in the present study was higher than that in the previous study (73.0 vs 62.9 years). Age is an important contributory factor to the incidence of DVT 5,18 ) . Second, tourniquets were applied to the TKA patients in the present study but not to the THA patients in the previous study, and the use of a tourniquet is an important risk factor for DVT 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…First, the mean age of participants in the present study was higher than that in the previous study (73.0 vs 62.9 years). Age is an important contributory factor to the incidence of DVT 5,18 ) . Second, tourniquets were applied to the TKA patients in the present study but not to the THA patients in the previous study, and the use of a tourniquet is an important risk factor for DVT 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies have shown the incidence of venous thromboembolism following lower extremity arthroplasty to be roughly 4.0%. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Although there are a limited number of studies when the outcomes are compared, considerably variable results are reported that change between 4% and 12%. 14 15 The reason for this may be expressed as the nonstandard patients attending the hospitals, and patient groups included in the studies. Some of the mentioned studies recommend preoperative screening of DVT, however, some report that it does not have an additional advantage and therefore it is not essential.…”
Section: Discussionmentioning
confidence: 99%